ANALISIS ADOPSI E-COMMERCE TERHADAP KINERJA UMKM DESA PLERET - Zulfatun Ruscitasari; Taufiq Kamal; Nurna Pratiwi (Indonesian Journal of Business Intelligence (IJUBI), 2021)
The spread of Covid-19 has had a negative impact on the business world, both small, medium and large scale. One of the strategies to deal with the impact of Covid-19 for SMEs is by adapting to technological advances 4.0 in order to keep up with the times.The main purpose of this study is to find out how the adoption of e-commerce in MSMEs in Pleret Village. In addition, to analyze the impact of adoption on the performance of SMEs. The approach used in this research is descriptive exploratory with the aim of exploring the field of study. The data analysis technique used was thematic analysis (Data Collection, Data Reduction, Data Presentation, Conclusions).The results of this study indicate that technology, organizational and environmental are factors that influence the adoption of e-commerce. However, the most dominant factor is the technology factor. As for the factors that affect the performance of MSMEs are increased sales, increased capital, increased labor, and increased profits, as well as an increase in the market. However, the most dominant factor of the impact of e-commerce adoption is sales growth.